The primer tRNA sequence is not inherited during Ty1 retrotransposition. - Lauermann, V (1994)
Yeast retrotransposon Ty1 transposes through an RNA intermediate by a mechanism resembling retroviral replication. Long terminal repeat retroelements require primers for initiation of reverse transcription. The primer for minus-strand DNA synthesis is the 3' end of a cellular tRNA that base pairs to the complementary region of genomic RNA (the primer binding site). The genomic RNA of retroviruses and retrotransposons is shorter than its proviral DNA counterpart, lacking complete long terminal repeats. A variety of models have been proposed to describe how complete long terminal repeats are regenerated during reverse transcription. A common feature of these models is the requirement that the 3' portion of the primer tRNA be reverse-transcribed and then utilized in a strand-transfer reaction. We introduced a silent mutation into the Ty1 primer binding site and followed its fate during a single cycle of reverse transcription to directly test this aspect of the reverse transcription model. We demonstrate that the tRNA sequence is not inherited by progeny Ty1 elements during reverse transcription.